Achieving the customized "rights" of logistics by adopting novel technologies: A conceptual approach and literature review - Seyhan Teoman (UTMS Journal of Economics, 2020)
From the early 2000s, with the rapid expansion and increasing complexity of supply chains, the logistics literature has frequently referred to "the seven rights of logistics (7Rs)" that linked business logistics to the key strategic objectives of cost competitiveness, quality, flexibility, and agility. The 7Rs are described as to deliver the "right product", in the "right quantity", in the "right quality", at the "right place", at the "right time" for the "right customer" and at the "right cost". The 7Rs suggest a generic roadmap for achieving efficiency, effectiveness, and a higher level of customer satisfaction in logistics services. However, within the last decade, customers' demand for customized products and services has increased dramatically. The generic 7Rs of logistics tends to differ for almost every individual customer, so the new focus is "the customized rights of logistics". This new paradigm forces businesses to explore and to experience new methods and tools to transform logistics processes to be faster, more flexible and more customer-oriented than ever before. The aim of this paper is to explore the benefit of adopting novel technologies in business processes to achieve the customized rights of logistics. Our research findings reveal that the adoption of novel technologies in logistics processes significantly leverages the ability of logistics service providers to offer customized solutions for their customers.
Keywords: M11; O33; 330; customized logistics; novel technologies; the seven rights of logistics